Establishment of the fetal-maternal interface: developmental events in human implantation and placentation - Huang, Chien-Chu; Hsueh, Ya-Wen; Chang, Chia-Wei; Hsu, Hsi-Chen; Yang, Tung-Chuan; Lin, Wu-Chou; Chang, Hsun-Ming (Frontiers in Cell and Developmental Biology, 2023)
Early pregnancy is a complex and well-orchestrated differentiation process that involves all the cellular elements of the fetal-maternal interface. Aberrant trophoblast-decidual interactions can lead to miscarriage and disorders that occur later in pregnancy, including preeclampsia, intrauterine fetal growth restriction, and preterm labor. A great deal of research on the regulation of implantation and placentation has been performed in a wide range of species. However, there is significant species variation regarding trophoblast differentiation as well as decidual-specific gene expression and regulation. Most of the relevant information has been obtained from studies using mouse models. A comprehensive understanding of the physiology and pathology of human implantation and placentation has only recently been obtained because of emerging advanced technologies. With the derivation of human trophoblast stem cells, 3D-organoid cultures, and single-cell analyses of differentiated cells, cell type-specific transcript profiles and functions were generated, and each exhibited a unique signature. Additionally, through integrative transcriptomic information, researchers can uncover the cellular dysfunction of embryonic and placental cells in peri-implantation embryos and the early pathological placenta. In fact, the clinical utility of fetal-maternal cellular trafficking has been applied for the noninvasive prenatal diagnosis of aneuploidies and the prediction of pregnancy complications. Furthermore, recent studies have proposed a viable path toward the development of therapeutic strategies targeting placenta-enriched molecules for placental dysfunction and diseases.